2020
DOI: 10.1038/s41598-020-62053-4
|View full text |Cite
|
Sign up to set email alerts
|

Study loading capacties of air pollutant emissions for developing countries: a case of Ho Chi Minh City, Vietnam

Abstract: , tam thoai nguyen, Hang thi thuy nguyen, Dung Minh Ho, Hien nhu nguyen & thuy thi thu nguyen * Ho chi Minh city (HcMc) is one of the cities in developing countries where many concentrations of air pollutants exceeded the Vietnam national technical regulation in ambient air quality including tSp, no x , ozone and co. these high pollutant concentrations have destroyed the human health of people in HcMc. Many zones in HcMc can't receive more air pollutants. the objectives of this research are: (i) Air quality mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Only the impact of CO 2 on urbanization is statistically significant in the short term. This empirical evidence may suggest that the government may focus on CO 2 emissions reduction policies by disintegrating industrial activities [131], reducing private vehicles [6], and collecting carbon taxes on automobiles and motorbikes [76] in large cities in the short term. As a result, these urbanization restrictions will improve environmental quality in the long run.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the impact of CO 2 on urbanization is statistically significant in the short term. This empirical evidence may suggest that the government may focus on CO 2 emissions reduction policies by disintegrating industrial activities [131], reducing private vehicles [6], and collecting carbon taxes on automobiles and motorbikes [76] in large cities in the short term. As a result, these urbanization restrictions will improve environmental quality in the long run.…”
Section: Discussionmentioning
confidence: 99%
“…Coal consumption accounts for between 65% and 75% of overall CO 2 emissions from the entire electricity sector, and oil consumption increases an average of 2.73% from 1977 to 2013 [4]. The excessive demand for natural resources and fossil-fuel energy due to the significant economic transformation has increased air pollution, especially in big cities where traffic congestion and industrial issues have become more serious [5,6]. For example, according to Our World in Data [7] and Euromonitor Passport Database [8], the average increase in carbon dioxide (CO 2 ) emissions reached 5.14%, along with the 6.53% increase in energy consumption and a 4.62% increase in real income for the period 1977 to 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, there has been a lack of works focusing on evaluating the overall impact of PM 2.5 as well as SO 2 and NO 2 on public health for HCMC. In 2019, an air pollution map over HCMC for many contaminations was released [4], together with the estimation of air emissions loading capacity for O 3 , NO 2 , SO 2 , and CO [11]. However, a PM 2.5 concentration map has not been available for HCMC.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with the urbanization process and related environmental degradation throughout Vietnamese cities, rapid expansion of urban areas in Ho Chi Minh City has resulted in lower environmental quality, particularly the air quality, over the last few decades (Ho et al 2020 ). In addition, a number of recent studies have reported urban heat island effects in this megacity in southern Vietnam (e.g.…”
Section: Study Areamentioning
confidence: 99%